Overuse injuries in female infantry recruits during low-intensity basic training - Finestone, A.; Milgrom, C.; Evans, R.; Yanovich, R.; Constantini, N.; Moran, D. S. (Medicine & Science in Sports & Exercise, 2008)
Purpose: The purpose of this prospective study was to investigate the epidemiology of overuse injuries and to identify common risk factors for stress fractures among female and male recruits in a new light infantry basic training designed to minimize the incidence of overuse injuries.